Implementation Of PAI Teacher Competence in Fostering Student’s Religious Tolerance at Mutia Rahma School Bulu Cina Hamparan Perak - Azhara, Siti; Holid, Syahrul (Lembaga Riset Mutiara Akbar, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in fostering an attitude of inter-religious tolerance at Mutia Rahma Bulu Cina School, Hamparan Perak. The method used was qualitative, with a descriptive approach to explore the experien ces and views of teachers and students. The results showed that PAI teachers, through various religious activities and interactive teaching, succeeded in instilling the values of tolerance and mutual respect among students. Despite facing challenges such as community prejudice, the commitment and dedication of PAI teachers play an important role in creating a conducive learning atmosphere. This research confirms the important role of religious education in shaping a more tolerant and harmonious generation. It confirms that the role of religious education is not only important for the school environment, but also has a long-term impact on society. By instilling attitudes of tolerance, religious education can contribute to reducing the potential for social conflict and promoting interfaith harmony. Overall, the results of this study show that PAI teachers have a great responsibility in shaping a more tolerant and cultured generation.